in pulmonary fibrosis induced by bleomycin in rats on the effects of inflammation and fibrosis of erdosteine - Erden, Ersin Sukru; Kirkil, Gamze; Deveci, Figen; Ilhan, Nevin; Cobanoglu, Bengu; Turgut, Teyfik; Muz, Mehmet Hamdi (Turkish Assoc Tuberculosis & Thorax, 2009)
[Abstract Not Available]